(untitled) (AYUSHDHARA, 2025)
Infertility is defined as the inability to conceive with in one or more years of regular unprotected coitus. Out of the many factors, tubal factors causing infertility account for about 25-30 % of all cases of infertility. The goal of the current treatment was to manage PCOD through Ayurvedic practices, aiming to promote regular ovulation and ultimately support a healthy pregnancy and successful childbirth. According to Ayurvedic principles, this case was diagnosed as Vandhyatva (infertility) due to Nashtartava (which can be associated with Polycystic Ovarian Disease) and tubal blockage, which is linked to Artava Vaha Strotosangha. Here is a case study of a 27-years-old female patient residing in Jaipur who consulted in OPD of the National Institute of Ayurveda (NIA) Jaipur on 26-7-23 with the chief complaint of being unable to conceive in the last 6 years and associated complaint of burning micturition since 6 years (on/off). Her hysterosalpingography findings were suggestive of patent right fallopian tube, partial block of left fimbria end, mild dilatation of fimbria end of both tubes. And ultrasound sonography was suggestive bilateral small ovarian haemorrhagic cyst. The patient was treated with Yoga basti (Anuvasana basti with Dashmool tail and Triphaladi taila and Aasthapana basti with Dashmool kwath, Punarnavashtak kwath, Erandmool kwath, Amalaki churna) for 2 cycles, with oral ayurvedic medicine. The patient missed her period on 30-11-23 and did her urine pregnancy test on 06-01-24, which was found to be positive. From this case study, it is concluded that Yoga basti are effective in treating infertility due to partial tubal block.